Hernia diafragmática congénita. Experiencia en el Hospital Universitario San Vicente de Paúl, Medellín, Colombia, 1999-2009 (2012)
ABSTRACT: Congenital diaphragmatic hernia (CDH) remains a challenge because of the wide variability of its clinical presentation, severity of respiratory failure, and the possibility of severe pulmonary hypertension. The objective of this review was to describe the management and outcomes of patients with CDH between 1999 and 2009, in the pediatric surgery unit at Hospital Universitario San Vicente de Paul in Medellín, Colombia. Materials and methods: We studied in 36 patients the socioeconomic variables, preoperative stabilization time, type of treatment, outcomes, complications, length of stay in the ICU, need for ventilatory support, and length of hospital stay. Results: HDC was more frequent on the left side and in males. Twenty two patients had associated malformations. Surgical treatment was carried out in 31 patients. Preoperative stabilization time averaged four days. The median duration of mechanical ventilation was four days, average stay in the ICU was six days and average hospital stay, 12.5 days. Sepsis was the most common complication, six patients had surgical site infection and an equal number had sequels. Ten patients died. Factors associated with mortality were hemodynamic instability, prenatal diagnosis, Apgar <5, lack of surgical treatment, use of patch for repair, and the presence of associated malformations.